2018
DOI: 10.3389/fmicb.2018.00898
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in the Food Industry: Health Aspects and Control Methods

Abstract: Diverse microorganisms are able to grow on food matrixes and along food industry infrastructures. This growth may give rise to biofilms. This review summarizes, on the one hand, the current knowledge regarding the main bacterial species responsible for initial colonization, maturation and dispersal of food industry biofilms, as well as their associated health issues in dairy products, ready-to-eat foods and other food matrixes. These human pathogens include Bacillus cereus (which secretes toxins that can cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
402
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(477 citation statements)
references
References 173 publications
(206 reference statements)
3
402
0
12
Order By: Relevance
“…The antiadhesive activity of biosurfactants is also an important property particularly if you are seeking to prevent biofilm formation (Galié et al . ). Biofilm formation plays a key role in the survival of both pathogenic (Kumar et al .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
“…The antiadhesive activity of biosurfactants is also an important property particularly if you are seeking to prevent biofilm formation (Galié et al . ). Biofilm formation plays a key role in the survival of both pathogenic (Kumar et al .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 97%
“…EPS may provide exceptional structural support for the biofilm and constitute the immediate environment of biofilm cells. Biofilms are virtually ubiquitous and are found in many habitats, including the dairy processing environment . In the dairy environment, biofilms can be found on practically all types of product contact surfaces, from milk cups on a dairy farm to heat exchangers in a processing plant .…”
Section: Biofilm‐forming Bacteria Contaminate Dairy Food and Deteriormentioning
confidence: 99%
“…Biofilms are virtually ubiquitous and are found in many habitats, including the dairy processing environment. 4,30 In the dairy environment, biofilms can be found on practically all types of product contact surfaces, from milk cups on a dairy farm to heat exchangers in a processing plant. 19,28,31 It has also been shown that bacteria could form floating biofilms such as pellicles and biofilm bundles during growth within milk.…”
Section: Biofilm-forming Bacteria Contaminate Dairy Food and Deteriormentioning
confidence: 99%
“…Bacteria growing as a biofilm are more tolerant of the presence of toxic compounds [1, 2] and predation by protists [3, 4], and exhibit increased persistence during infection due to antimicrobial tolerance [5, 6] and the ability to evade the host immune response [7, 8]. As a result, biofilm formation is linked not only to chronic bacterial infection in humans [9] [10], and plants and animals of economic importance [1113], but also to the contamination of industrial facilities involved in processing food [14, 15], and pulp and paper [16].…”
Section: Introductionmentioning
confidence: 99%